2013
DOI: 10.1007/s10495-013-0805-y
|View full text |Cite
|
Sign up to set email alerts
|

Tiron and trolox potentiate the autophagic cell death induced by magnolol analog Ery5 by activation of Bax in HL-60 cells

Abstract: This study describes the mechanism of trolox and tiron induced potentiation of cytotoxicity caused by Ery5, an analog of magnolol, in human myeloid leukemia HL-60 cells. Ery5 induced cytotoxicity in HL-60 cells by involving activation of bax and cleavage of caspase 3, which contributed towards activation of both apoptotic and autophagic pathways. Trolox and tiron, even at non-toxic concentrations, contributed to the cytotoxicity of Ery5 by activation of autophagic proteins like ATG7, ATG12 and LC3-II. Z-VAD-fm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
8
16
0
Order By: Relevance
“…As mentioned, the increase of LC3-II that we observe with western blotting analysis despite a clear block of autophagosome formation has been previously reported in cells treated with Trolox, but the results in this report are in the absence of any confocal or IF data showing LC3 localization [47]. Consistent with our results it has been reported that many other antioxidants block autophagy [65].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As mentioned, the increase of LC3-II that we observe with western blotting analysis despite a clear block of autophagosome formation has been previously reported in cells treated with Trolox, but the results in this report are in the absence of any confocal or IF data showing LC3 localization [47]. Consistent with our results it has been reported that many other antioxidants block autophagy [65].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, when we treated RP-deficient zebrafish embryos with 10 mM Trolox overnight we observed a substantial decrease in the levels of S6 kinase phosphorylation in embryos carrying mutations in rpS7 or rpS3a , which in turn alleviated the inhibition of AKT phosphorylation activity (Figure 7D). Interestingly, the Trolox treatment while clearly blocking autophagosome formation in the GFP-LC3 HEK cells was unexpectedly coupled to an increase of LC3-II by western blotting analysis (Supporting Figure S2), the latter a feature of Trolox that has been previously reported [47]. However, in the same cells we also find that Trolox results in an increase of p62 expression and a decrease of phosphorylated S6 kinase, supporting the confocal results indicating that there is a block of autophagy due to a reduction of S6 kinase signaling (Supporting Figure S2).…”
Section: Resultssupporting
confidence: 69%
“…Magnolol is a natural compound that has been studied to have anticancer potential by showing antiproliferative activity against different cancer cell lines through the induction of apoptosis or autophagy. 29, 30 …”
mentioning
confidence: 99%
“…(13) However, when this process occurs in excess, autophagy itself becomes cytotoxic and eventually leads to autophagic cell death. (14) Thus, in addition to apoptotic cell death, the study on autophagic response is a prospective direction for the development of anticancer drugs. Reactive oxygen species (ROS) production, especially through the mitochondria, is important for the regulation for autophagy induction in cancer therapy.…”
mentioning
confidence: 99%